Cognitive Function, Coping, and Depressive Symptoms in Children and Adolescents with Sickle Cell Disease. (16th November 2017) - Prussien, Kemar V; DeBaun, Michael R; Yarboi, Janet; Bemis, Heather; McNally, Colleen; Williams, Ellen; Compas, Bruce E
Abstract: Objective: The objective of this study was to investigate the association between cognitive functioning, coping, and depressive symptoms in children and adolescents with sickle cell disease (SCD). Method: Forty-four children ( M age = 9.30, SD = 3.08; 56.8% male) with SCD completed cognitive assessments measuring working memory (Wechsler Intelligence Scale for Children-Fourth Edition) and verbal comprehension (Wechsler Abbreviated Scale of Intelligence-Second Edition). Participants' primary caregivers completed questionnaires assessing their child's coping and depressive symptoms. Results: Verbal comprehension was significantly positively associated with secondary control coping (cognitive reappraisal, acceptance, distraction), and both working memory and secondary control coping were negatively associated with depressive symptoms. In partial support of the primary study hypothesis, verbal comprehension had an indirect association with depressive symptoms through secondary control coping, whereas working memory had a direct association with depressive symptoms. Conclusions: The results provide new evidence for the associations between cognitive function and coping, and the association of both of these processes with depressive symptoms in children with SCD. Findings provide potential implications for clinical practice, including interventions to improve children's cognitive functioning to attenuate depressive symptoms.